2016
DOI: 10.1016/j.fertnstert.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Short-term hypothermic preservation of human testicular tissue: the effect of storage medium and storage period

Abstract: Objective: To optimize the storage medium and period during short-term preservation of human testicular tissue. Design: First, human testicular tissue fragments from five patients were kept at 4 C for 3 days in different media (Dulbecco's modified Eagle's medium [DMEM]/F12, DMEM/F12 þ 20% human serum albumin [HSA], DMEM/F12 þ 50% HSA, and HSA). Secondly, fragments from four patients were kept in DMEM/F12 for 3, 5, or 8 days at 4 C. Setting: Laboratory research environment. Patient(s): Adult human testicular ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…A previous study reported that immature non-human primate testicular tissues that had been cold stored for 24 hours could be xenografted and initiate spermatogenesis up to the spermatocyte stage (Jahnukainen et al ., 2007). Human testicular tissues have been cold stored for up to 3 days at 4°C without altering tissue morphology, Sertoli cell morphology, number of spermatogonia, or number of apoptotic cells (Faes and Goossens, 2016). Collectively, these data suggest that some period of cold storage during shipping may be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that immature non-human primate testicular tissues that had been cold stored for 24 hours could be xenografted and initiate spermatogenesis up to the spermatocyte stage (Jahnukainen et al ., 2007). Human testicular tissues have been cold stored for up to 3 days at 4°C without altering tissue morphology, Sertoli cell morphology, number of spermatogonia, or number of apoptotic cells (Faes and Goossens, 2016). Collectively, these data suggest that some period of cold storage during shipping may be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, testicular cryopreservation is a reproductive biotechnology of great importance in the recovery and conservation of genetic material from prepubertal animals belonging to endangered wild species (Pukazhenthi et al., ), as well as in the preservation of reproductive potential of animals with higher zootechnical importance, which have died early or who have undergone treatments that cause infertility, or for patients suffering from testicular tumours undergoing chemotherapy or radiotherapy (Faes & Goossens, ).…”
Section: Introductionmentioning
confidence: 99%
“…This raises concern about the quality of ITT when shipment to the banking facility is delayed. Earlier study in human ITT showed no change in the structural integrity up to 3 days of holding at 4 °C [ 13 ]. However, in our study, after 14 days of in vitro culture, the cell viability, testosterone production, and the number of postmeiotic population were identical across both ultraprofound and profound-hypothermic-temperature groups and at both 6 h holding, but significantly reduced in 24 h holding at profound-hypothermic-temperature.…”
Section: Discussionmentioning
confidence: 99%
“…If the retrieved ITT can be cryopreserved with minimal manipulation, the chance to recover optimum number of cells for fertility restoration techniques might increase [10]. Hence, earlier studies have addressed the effects of varying tissue size, storage temperatures, and storage periods in porcine model [10] and in human [11][12][13][14], to recommend the ideal conditions. No loss of cell viability and structural integrity was observed during the length of cooling [10], and proliferative potential was unaltered when cooled tissue was thawed and xenografted [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation